2011
DOI: 10.1096/fj.11-190934
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine promotes alternative macrophage activationviaA2A and A2B receptors

Abstract: Adenosine has been implicated in suppressing the proinflammatory responses of classically activated macrophages induced by Th1 cytokines. Alternative macrophage activation is induced by the Th2 cytokines interleukin (IL)-4 and IL-13; however, the role of adenosine in governing alternative macrophage activation is unknown. We show here that adenosine treatment of IL-4- or IL-13-activated macrophages augments the expression of alternative macrophage markers arginase-1, tissue inhibitor of matrix metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
253
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(270 citation statements)
references
References 54 publications
14
253
2
1
Order By: Relevance
“…Arg1 expression via STAT3-dependent 54 and cAMP-mediated pathways 55,56 have been previously reported. Furthermore, although it was recently reported that adenosine augments IL-4-induced alternative activation in macrophages, 57 we did not observe enhanced expression of any AAMspecific biomarkers in TLR-activated macrophages exposed to ATP. Together, these observations indicate that TLR-activated macrophages exposed to eATP represent a state of activation distinct from AAMs.…”
Section: Discussioncontrasting
confidence: 96%
“…Arg1 expression via STAT3-dependent 54 and cAMP-mediated pathways 55,56 have been previously reported. Furthermore, although it was recently reported that adenosine augments IL-4-induced alternative activation in macrophages, 57 we did not observe enhanced expression of any AAMspecific biomarkers in TLR-activated macrophages exposed to ATP. Together, these observations indicate that TLR-activated macrophages exposed to eATP represent a state of activation distinct from AAMs.…”
Section: Discussioncontrasting
confidence: 96%
“…This indicates a distinct mechanism governing the antimetastatic effect of A 2B antagonism. A 2B activation is known to modulate several subsets of myeloid cells, including dendritic cells (21,(30)(31)(32), macrophages (19,33,34) and MDSCs (20). Notably, in the context of the primary tumor site, it has been reported that A 2B blockade could enhance the expression of CD86 on CD11b − dendritic cells and consequently induce more potent antitumor immune responses (18).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data indicate that the expression of CD73 on tumor cells enhances metastasis through increased A 2A -mediated suppression of perforin-mediated NK cell cytotoxicity. Because A 2B blockade has previously been shown to modulate the differentiation of MDSCs and the function of macrophages and dendritic cells (18)(19)(20), we investigated the impact of A 2B blockade on these immune subsets in the metastatic setting. A 2B blockade did not modulate the frequency of CD11b + (dendritic cells) subsets was unaltered in mice treated with the A 2B antagonist PSB-1115.…”
Section: Activation Of a 2a Adenosine Receptors Enhances Metastasis Tmentioning
confidence: 99%
“…In TAM in mice, experiments with STAT1 and STAT6 knockout mice initially suggested that ARG1 activity may be primarily dependent on STAT1 (26). More recent reports in murine alternatively activated macrophages demonstrated that STAT3 can regulate ARG1 (22,29). Moreover, human MDSC's immunosuppressive activity from cancer patients was found to be STAT3 dependent (18,19).…”
Section: Figurementioning
confidence: 99%
“…Marigo et al showed that C/EBPβ transcription factor in the myeloid compartment is critical in regulating immunosuppression (20), and Zhang et al showed that STAT3 directly controls G-CSF-dependent expression of C/EBPβ in emergency granulopoiesis (21). C/EBPβ has been shown to regulate arginase-I (ARG1) in murine macrophages (22). In other murine studies, inhibition of STAT3 signaling in the myeloid compartment induced an antitumor response (23).…”
Section: Introductionmentioning
confidence: 99%